Failure of voriconazole therapy due to acquired azole resistance in Aspergillus fumigatus in a kidney transplant recipient with chronic necrotizing aspergillosis. Issue 9 (12th July 2018) - Pilmis, Benoit; Garcia‐Hermoso, Dea; Alanio, Alexandre; Catherinot, Emilie; Scemla, Anne; Jullien, Vincent; Bretagne, Stéphane; Lortholary, Olivier
Abstract : Invasive aspergillosis (IA) affects the lungs and disseminates mostly in patients with neutropenia and/or patients who are receiving immunosuppressive and steroid therapies. Despite progress in the diagnosis of and therapy for IA, it is still characterized by a high mortality rate. Currently, voriconazole is considered as the standard therapy for IA. Over recent years, triazole‐resistant Aspergillus fumigatus isolates have emerged in the environment due to the use of fungicidal agricultural products, with the risk of developing IA related to a resistant isolate. However, resistance may also develop in patients who are undergoing long‐term triazole therapy, particularly in the setting of chronic forms of pulmonary aspergillosis. Herein we describe a kidney transplant recipient who failed to respond to voriconazole therapy due to acquired resistance secondary to the appearance of a de novo mutation (Y121F) in the cyp51A gene during chronic necrotizing pulmonary aspergillosis. The infecting isolate acquired voriconazole resistance in 8 months despite plasma concentrations within the recommended range of the drug, necessitating lobectomy in association with a new antifungal strategy consisting of liposomal amphotericin and caspofungin with a good outcome over 36 months. Abstract : Unfavorable clinical evolution of pulmonary aspergillosis when under appropriate treatment must be tested with genotypic analysis in search of resistant strains.